Response to the Letter to the Editor: Prevalence, Risk Factors and Assessment of Depressive Symptoms in Patients With Systemic Sclerosis - Christine MARCH; Dörte HUSCHER; Emelina PREIS; Alexander MAKOWKA; Jakob HOEPPNER; Frank BUTTGEREIT; Gabriela RIEMEKASTEN; Kristina NORMAN; Elise SIEGERT (Archives of Rheumatology, 2020)
Thank you very much for your interest in our article “Prevalence of Depressive Symptoms in Patients with Systemic Sclerosis”. We value your contribution to central questions on prevalence and relevance of depressive disorders in this field and are glad to respond to your concerns. We are fully aware that the Major Depression Inventory (MDI) does not allow us to diagnose depressive disorders or to estimate its prevalence among patients with systemic sclerosis (SSc). At no point in our study did we claim that we assessed the prevalence of depression in SSc.[1] You might be right that the scientific value of estimating the prevalence of MDI-relevant items is limited. However, as we mention in the discussion of our paper, we want to raise the awareness for mental health issues in SSc without providing psychiatric diagnoses, measuring significant impairment or estimating the prevalence of depressive disorders in SSc. Also, we did not evaluate the MDI as a screening tool for depressive disorders in SSc. Our primary interest was to assess the number of patients suffering from depressive symptoms and who might thus benefit from systematic evaluation of mental health issues. We share your concerns regarding the overestimation of depressive disorders by depression symptom questionnaires. However, we chose the MDI because it is known to be a rather conservative measure for depressive symptoms according to comparative studies using other self-report questionnaires.[2] At the same time, it is short enough to be handed out to patients in an out-patient setting. Hence, it might potentially serve as a screening tool; to evaluate this was not the aim of your study. Of note, as mentioned in our paper, we were able to confirm a lower prevalence of these symptoms than stated in other studies.[3-9] This is in line with previous findings from Nielsen et al.[2] indicating that the MDI is a more conservative tool and which may support the idea that the MDI should be evaluated as a screening tool for depressive disorders in SSc.